Studi Pakan Burung Perkici Pelangi (Trichoglossus haematodus Linnaeus, 1771) dalam Laboratorium Penangkaran - W. Widodo (Universitas Atma Jaya Yogyakarta, 2007)
During the 2002-2003 period, the research was done to study 11 Rainbow Lorikeets reared in an animal house laboratory. The aim of this research was to find the food rations formule of the Rainbow Lorikeets so that those birds can be able to grow and breed well. The food rations were composed of 26.3% local bird foods (521), 35.09% lampung bananas, 8.77% slice corns, 10.5% boiled quails eggs, 1.75% white bread, bean sprouts and red sugar are 8.77%, respectively. All of food materials were mixed on the plastic cup and mixed with 450 ml of water, then pulverized like sweet porridge. That porridge was given to birds in cafeteria and the water was made ready “ad libitum” everyday. The results have shown that giving food rations formula can stimulate two pairs of the Rainbow Lorikeets breeding and during the 2002-2003 period they produced three young birds.